Análisis Multitemporal de la Cobertura del Suelo Afectada por Incendios Forestales en la Reserva Forestal Protectora Bosque Oriental de Bogotá, Utilizando Google Earth Engine. Enero de 2024 (2025)
The multitemporal analysis carried out for the development of this document highlights the changes in ground cover affected by the forest fire that occurred in January 2024 in the Forest Reserve Protectorate Bosque Oriental de Bogotá. Landsat 8 images corresponding to two specific moments before and after the fire, captured on December 12, 2023, and January 27, 2024, respectively, were used for this purpose. Burn Ratio Index (NBR), Burned Area Index (BAI), and Normalized Difference Vegetation Index (NDVI) were calculated on these images, allowing for the identification of fire intensity, size, and vegetation cover affected. These calculations were performed using the Google Earth Engine platform through ArcGIS Pro software and its Gee Map module on the Notebook.